Estimating Palatal and Pharyngeal Muscle Contraction in Hindi Syllable Pronunciation using Computational Modeling - Madhubari Vathulya; Subrato Sarkar; Indra Vir Singh; Tripta Prajapati; Pankaj Sharma (Indian Journal of Plastic Surgery)
Introduction Speech, one of the main functions affected by cleft palate, involves a complex orchestra of sound deformation by various organs including the larynx, pharynx, epiglottis, palate, tongue, lip, and other structures complementing them. Although the effects of palatoplasty are traditionally evaluated subjectively, objective parameters have seldom been described to compare the pre- and postrepair functions. The study tries to extract the palatal and pharyngeal muscles while uttering various Hindi syllables and tries to find the percentage contraction of these structures as an objective assessment.